Dampak Permainan Kekerasan Online Terhadap Karakter Anak: Sistematik Literatur Review - Mirzon Daheri; Ahmad Zain Sarnoto; Slamet Riyadi; St. Rahmah; Singgih Prastawa (Departement of Mathematics Education, 2023)
Online games are played through internet connection on various devices, either alone or collaboratively with players from around the world. This research aims to explore the impact of violence in online games on children's behavior and mental health. The research methodology is literature review, using sources from Google Scholar and articles published in Scopus- and Sinta-accredited journals. Violence in online games refers to graphic or action scenes that depict violence, such as weapon fighting, physical violence, harsh language, or other brutal acts. Some games display violence explicitly and realistically, such as blood, broken bones, or sexual violence, while in other games, violence is implicitly and less visible. The presence of violent content in online games may have different impacts on children, but generally can affect their behavior, character, and mental health. Therefore, it is crucial for parents and caregivers to limit the time spent playing online games and choose games that are safe and do not contain violent content for children. The negative impact of violent online games includes increased aggression, reduced empathy, decreased mental health, distraction, and worsened behavior. However, there are also positive impacts of violent online games, such as enhancing social and cognitive skills, improving multitasking ability, and boosting creativity. It is important for parents and caregivers to monitor and regulate their children's online game time, and choose games appropriate for their age and maturity level that do not contain violent content.